Implementation of quantum rotation gates using controlled non-adiabatic evolutions - Abdelrahim, Abdelrahman A. H; Mahmoud Ahmed, Gharib Subhi; Turaev, Sherzod; Az Eddine, Messikh (World Academy of Science, Engineering and Technology ( WASET ), 2018)
Quantum gates are the basic building blocks in the quantum circuits model. These gates can be implemented using adiabatic or non adiabatic processes. Adiabatic models can be controlled using auxiliary qubits, whereas non adiabatic models can be simplified by using one single-shot implementation. In this paper, the controlled adiabatic evolutions is combined with the single-shot implementation to obtain quantum gates with controlled non adiabatic evolutions. This is an important improvement which can speed the implementation of quantum gates and reduce the errors due to the long run in the adiabatic model. The robustness of our scheme to different types of errors is also investigated. Keywords—Adiabatic evolutions, non adiabatic evolutions, controlled adiabatic evolutions, quantum rotation gates, dephasing rates, master equation.